'Blood in pee' campaign: Increased demand on secondary care with no change in cancers diagnosed. (January 2019) - Patel, Kunjan; Hall, Susan Jane; Shraddha, Kamath; Stanford, Richard; Williams, Simon; Lund, Jon
Objective: As part of the national Be Clear on Cancer campaign, the 'blood in pee' campaign was launched in 2013. We aimed to evaluate the impact of the campaign on 2-week wait (2WW) referrals and the resulting diagnoses of malignancy at a single trust, and secondly, to evaluate the socio-economic background of patients referred. Patients and methods: Suspected cancer 2WW patients in the 3 months pre- and post-campaign were included. Demographics, investigations and diagnoses were recorded. A Kolmogorov–Smirnov test demonstrated a normal distribution. The data were treated as parametric and analysed with the unpaired Student's t -test. Results: Referrals for visible haematuria significantly increased by 52% from 135 pre-campaign to 205 post-campaign ( p = 0.03). There was a fall in the proportion of patients diagnosed with malignancy from 20.27% pre-campaign to 15.36% post-campaign. The mean index of multiple deprivation score of referrals did not change: p = 0.43. Conclusion: This campaign has increased referrals without increasing the proportion of malignancies diagnosed, placing large demand on services without benefit or extra funding. Nor has the campaign effectively reached deprived socio-economic groups. There is little evidence as to the efficacy of untargeted cancer awareness campaigns and further work is needed to improve their pick-up of malignancies. Level of evidence: 2C